Hypoxia-Induced MALAT1 Promotes the Proliferation and Migration of Breast Cancer Cells by Sponging MiR-3064-5p - Shih, Chung-Hsien; Chuang, Li-Ling; Tsai, Mong-Hsun; Chen, Li-Han; Chuang, Eric Y.; Lu, Tzu-Pin; Lai, Liang-Chuan (Frontiers in Oncology, 2021)
Hypoxia, a common process during tumor growth, can lead to tumor aggressiveness and is tightly associated with poor prognosis. Long noncoding RNAs (lncRNAs) are long ribonucleotides (>200 bases) with limited ability to translate proteins, and are known to affect many aspects of cellular function. One of their regulatory mechanisms is to function as a sponge for microRNA (miRNA) to modulate its biological functions. Previously, MALAT1 was identified as a hypoxia-induced lncRNA. However, the regulatory mechanism and functions of MALAT1 in breast cancer are still unclear. Therefore, we explored whether MALAT1 can regulate the functions of breast cancer cells through miRNAs. Our results showed the expression levels of MALAT1 were significantly up-regulated under hypoxia and regulated by HIF-1α and HIF-2α. Next, in contrast to previous reports, nuclear and cytoplasmic fractionation assays and fluorescence in situ hybridization indicated that MALAT1 was mainly located in the cytoplasm. Therefore, the labeling of MALAT1 as a nuclear marker should be done with the caveat. Furthermore, expression levels of miRNAs and RNA immunoprecipitation using antibody against AGO2 showed that MALAT1 functioned as a sponge of miRNA miR-3064-5p. Lastly, functional assays revealed that MALAT1 could promote cellular migration and proliferation of breast cancer cells. Our findings provide evidence that hypoxia-responsive long non-coding MALAT1 could be transcriptionally activated by HIF-1α and HIF-2α, act as a miRNA sponge of miR-3064-5p, and promote tumor growth and migration in breast cancer cells. These data suggest that MALAT1 may be a candidate for therapeutic targeting of breast cancer progression.